A Study of English Phonology of Yoruba Speakers of English as a Second Language: A Re-examination of some Linguistic Problem Areas. - Dairo, Anthony Lekan (Obafemi Awolowo University, 2014)
Over the years linguists have discovered some sounds that constitute problems for Yoruba speakers of English as a second language and such sounds have been found to be responsible for the deviations in their English speech performances. The contrastive linguists who have worked so far on Yoruba-English comparison have limited their efforts to the standard forms of the two languages.